Numerical and Simulation Study of Cavitation in Centrifugal Pump at Low Flow Rate - Nurul Azlien Abd Khalid; Rohani Rahmad (Journal of Advanced Industrial Technology and Application, 2022)
Cavitation is the compressible and unsteady turbulent flow caused by the mass transfer between gas and liquid phase which has significant influence on the operating stability and service life of a centrifugal pump. Cavitation can form in a fluid because of localised decreases in dynamic pressure. The collapse of vapour cavities created extremely high pressures, which usually damage neighbouring surfaces and lead to reduce performance. This study aims to simulate a computational model of the cavitation flow using ANSYS Fluid Flow (Fluent). Next, to determine the cavity volume fraction in a centrifugal pump at low flow rate. In this study, the design point of the centrifugal pump used a rotational speed of pump motor at 1450 rpm and initial inlet pressure at 2500 kPa. The simulation of the cavity volume fraction was conducted with four different HNPSHa value, which are 2.09, 1.43, 1.32 and 1.21 m at 25°C of water temperature. The result shows that the values of HNPSHa did affect the cavity volume fraction of pump impeller. Its shows that the decreasing in HNPSHa value, the cavity volume fraction is increased. This study came out with the simulation analysis that predicts a cavitation of the centrifugal pump at different HNPSHa values. The outcomes of this study may help the future researcher to understand how cavitation occurs at low flow rate and its relationship between HNPSHa values